2020
DOI: 10.1111/jfpp.15120
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity ofEryngium campestreL.,Froriepia subpinnata, andMentha spicataL. polyphenolic extracts nanocapsulated in chitosan and maltodextrin

Abstract: The antioxidant activity of Eryngium campestre, Froriepia subpinnata, and Mentha spicata polyphenolic extracts nanocapsulated in chitosan (CS) and maltodextrin (MD), and incorporated in canola oil under accelerated oxidation condition was evaluated. The zeta potential of nanoemulsions coated with 10%MD, 9.5%MD:0.5%CS, 9%MD:1%CS, and 8.5%MD:1.5%CS was −7.51 to −7.68, −0.06 to −0.08, 1.20 to 1.25, and 1.85 to 1.89 mV, respectively, also the average particle size was 52.73–52.91, 50.33–50.73, 26.05–27.29, and 15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, a total of five flavonoids were detected, namely kaempferol, quercitrin (absent in shoots), rutoside (undetected in roots), quercetin, and astragalin [49]. Azizkhani and Sodanlo [50] reported that the methanol extract of E. campestre exhibited a total phenolic compound content of 120.5 ± 4.2 mg GAE/g of dry extract. In a study conducted by Güneş et al [27], it was found that the flowers and leaves of E. campestre contained a total phenolic compound content of 116.69 mg and 109.62 mg GAE/mL of plant extract, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a total of five flavonoids were detected, namely kaempferol, quercitrin (absent in shoots), rutoside (undetected in roots), quercetin, and astragalin [49]. Azizkhani and Sodanlo [50] reported that the methanol extract of E. campestre exhibited a total phenolic compound content of 120.5 ± 4.2 mg GAE/g of dry extract. In a study conducted by Güneş et al [27], it was found that the flowers and leaves of E. campestre contained a total phenolic compound content of 116.69 mg and 109.62 mg GAE/mL of plant extract, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The highest encapsulation efficiency was observed for M. spicata extract encapsulated in 8.5% maltodextrin and 1.5% chitosan. E. Campestre extract nanoencapsulated in 8.5% maltodextrin and 1.5% chitosan possessed the highest antioxidant activity in canola oil (Azizkhani & Sodanlo, 2021). These NE systems therefore can be employed for encapsulation of plant extracts and their consequent application in food systems.…”
Section: Encapsulation Of Polyphenols In Nanoemulsionsmentioning
confidence: 99%
“…In addition, F. subpinnata has antioxidant, anti-atherostatic, antimicrobial, and antiviral properties. The constituents of P. granatum include gallocatechin, delphinidin, cyanidin, gallic acid, ellagic acid, pelargonidin, and sitosterol, which are well-known due to their therapeutic properties (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%